Analisis Legalitas Transaksional Binary Option di Indonesia - Nola Alfiona Kumala (Jurist-Diction, 2024)
Abstract The development of financial technology has given birth to a new financial transaction, namely Binary Options. Binary Options market their products as an investment that promises fixed profits, giving rise to public misconceptions as an investment. The Commodity Futures Trading Supervisory Agency has stated that Binary Options do not comply with the provisions of Indonesian laws and regulations. The aim of this research is to analyze the legality of Binary Option transactions. This research is legal research that uses a statutory approach and a conceptual approach. Binary Options have high risks because they are not registered on an exchange and are vulnerable to fraud. There is a need for comprehensive regulations relating to Binary Option transactions in Indonesia. This article will explain that Binary Options cannot be categorized as a form of investment. Furthermore, this article will explain that from a criminal law perspective, speculative Binary Option transactions can be categorized as a form of gambling.   Keywords: Binary Option, Commodity Future Exchange, Legality.   Abstrak Perkembangan teknologi finansial dan instrumen keuangan telah melahirkan suatu transaksi keuangan baru yaitu Binary Option. Binary Option memasarkan produknya sebagai suatu investasi yang menjanjikan keuntungan tetap, sehingga menimbulkan miskonsepsi masyarakat sebagai investasi. Badan Pengawasan Perdagangan Berjangka Komoditi telah menyatakan bahwa Binary Option tidak sesuai dengan ketentuan peraturan perundang-undangan di Indonesia. Tujuan dari penelitian ini adalah menganalisis legalitas transaksional Binary Option. Penelitian ini merupakan penelitian hukum yang menggunakan pendekatan perundang-undangan dan pendekatan konseptual. Binary Option memiliki risiko yang tinggi karena tidak terdaftar di bursa dan rentan akan penipuan, perlu adanya regulasi yang komprehensif berkaitan dengan transaksi Binary Option di Indonesia. Artikel ini akan menjelaskan bahwa Binary Option tidak dapat dikategorikan sebagai suatu bentuk investasi baik dalam pasar modal maupun pasar perdagangan berjangka. Terlebih lanjut, artikel ini akan menjelaskan dalam perspektif hukum pidana, transaksi Binary Option yang spekulatif dapat dikategorikan sebagai suatu bentuk perjudian.   Kata Kunci: Binary Option, Perdagangan Berjangka Komoditas, Legalitas.